INSTITUSIONALISASI PARADIGMA REVENUE CENTER UNTUK PENGELOLAAN ASET NEGARA YANG OPTIMAL (STUDI KASUS PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG SURABAYA) - Tridasa Novany Wijaya; Hamidah Hamidah (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
To realize good and accountable asset management, the Ministry of Finance as CFO (Chief Financial Officer) sets the revenue center paradigm in asset management. This is a new breakthrough from before that just as an asset administrator turns into asset manager without thinking about the potential revenue from asset management. The Directorate General of State Assets (DJKN) as the state asset manager with vertical institutions is implementing National Working Meeting (Rakernas) as the milestone of the beginning of the birth of this new paradigm with the stipulation of Circular Letter (Surat Edaran) Number 2/KN/2016 about the Following of the National Working Meeting DJKN 2016. Based on the mandate, The State Property and Auction Office of Surabaya (KPKNL Surabaya) continues to internalize this paradigm shift in order to realize the optimization of revenue through the management of state assets. The purpose of this study is to understand how the institutionalization process of this new paradigm by using new institutionalism theory. The methodology used in this research uses qualitative method with case study approach which is discussed with deep descriptive analysis. The results indicate the existence of institutional isomorphism symptoms that occur in the internalization process of this new paradigm, thus providing an overview of the influence and reaction to the establishment of a new paradigm that encourages organizational change.